2023
DOI: 10.15376/biores.18.1.1436-1453
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, social, and governance adoption in the Malaysian wood products and furniture industries: Awareness, adoption, and challenges

Abstract: As the world intensifies efforts to mitigate the effect of global climate change, an on-line survey was carried out involving 1,081 wood products and furniture manufacturers in Malaysia. The main objective was to evaluate the level of awareness, extent of adoption, and challenges faced by these manufacturers in adopting environmental, social, and governance (ESG) practices. The survey found that large-sized companies were more receptive to adopting ESG practices, as opposed to the medium-, small-, and micro-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Meanwhile, Building Related Illnesses (BRI) are closely related to prevailing poor IAP, and the impact of such poor building practices. In fact, with the growing concern for the Environment, Social and Governance (ESG) compliance, in line with the SDGs, such consideration will become increasingly important when designing and constructing homes and buildings in the future (Marques et al 2020;Mannan and Al-Ghamdi 2021;Ratnasingam et al 2023). The sick building syndrome (SBS) describes a situation in which building occupants experience acute health and/or comfort effects that appear to be linked to time spent in a particular building, but where no specific illness or cause can be identified (DOSH 2010).…”
Section: Implications Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Building Related Illnesses (BRI) are closely related to prevailing poor IAP, and the impact of such poor building practices. In fact, with the growing concern for the Environment, Social and Governance (ESG) compliance, in line with the SDGs, such consideration will become increasingly important when designing and constructing homes and buildings in the future (Marques et al 2020;Mannan and Al-Ghamdi 2021;Ratnasingam et al 2023). The sick building syndrome (SBS) describes a situation in which building occupants experience acute health and/or comfort effects that appear to be linked to time spent in a particular building, but where no specific illness or cause can be identified (DOSH 2010).…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…In this respect, it is imperative that the design and construction of buildings in the country be re-examined to ensure that the green building concepts are incorporated so that improved living comfort can be achieved. Traditional building design and construction of the past may no longer be viable on the basis of cost, as the general population becomes increasingly conscious of the need for improved living comfort and higher indoor air quality (Ratnasingam et al 2023). In terms of controlling and managing VOCs and formaldehyde emissions indoors, the authorities would need a wholesome approach, rather than a 'knee-jerk' guideline, which is insufficient to contain the problem, and in turn has an adverse impact on the wood products manufacturing industry.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a previous study by Ratnasingam (2018) showed that mistrust among Bumiputera entrepreneurs of their non-Bumiputera partners appears to be a major challenge in building a lasting business relationship. This calls for an open culture, of mutual respect, which is crucial as a foundation for forging a lasting business relationship, and so important to build a strong and resilient SC (Ratnasingam et al 2023). If the Bumiputera entrepreneurs focus on developing the above aspects, their capacity to consolidate and increase its power on partners and actors, to attract the voluntary collaboration would be improved significantly (Zekić and Samaržija 2017), allowing the entrepreneurs to actively source, process, and sell their products.…”
Section: Implications For Bumiputera Entrepreneurs In the Wood Produc...mentioning
confidence: 99%